2022
DOI: 10.1111/beer.12413
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact mechanism of environmental regulations on corporate environmental proactivity—based on the perspective of political connections

Abstract: Previous studies have demonstrated the favorable effects of political connections on corporate environmental proactivity (CEP). However, few studies have further verified whether this is definitively the case under environmental regulations and their underlying reasons, which would help elucidate the performance and motivation of politically connected firms’ (PCFs’) environmental proactivity. Using data from Chinese A‐shares‐listed industrial firms from 2010 to 2016, we find that environmental regulations can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Reactive environmental strategy refers to resultant behavior from deterrence and punishment by regulators (Gunningham et al, 2005), while proactive environmental strategy refers to such initiatives that not just focus on regulatory compliance but also systematically prevent damage to the environment (Hart, 1995; Wang et al, 2021). Effective implementation of a well‐designed environmental strategy capitalizes on unique organizational capabilities to bring competitive advantage, sustainable success, and natural environment protection (Davis et al, 2019; Ko & Liu, 2016; Yi & Wu, 2022). Growing research has identified organizations' commitment to reducing the negative impact or imprinting positive effects on the environment through the corporate environmental strategy (Uddin et al, 2021).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Reactive environmental strategy refers to resultant behavior from deterrence and punishment by regulators (Gunningham et al, 2005), while proactive environmental strategy refers to such initiatives that not just focus on regulatory compliance but also systematically prevent damage to the environment (Hart, 1995; Wang et al, 2021). Effective implementation of a well‐designed environmental strategy capitalizes on unique organizational capabilities to bring competitive advantage, sustainable success, and natural environment protection (Davis et al, 2019; Ko & Liu, 2016; Yi & Wu, 2022). Growing research has identified organizations' commitment to reducing the negative impact or imprinting positive effects on the environment through the corporate environmental strategy (Uddin et al, 2021).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In areas where the government is highly concerned about the environment, enterprises may be encouraged to implement substantive environmental management practices. Otherwise, they may suffer serious administrative penalties and lose policy support (Yi and Wu, 2022). In areas with lower governmental environmental concerns (GEC), corporate environmental management is only for short-term legal purposes, known as symbolic environmental management.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In areas where the government is highly concerned about the environment, enterprises may be encouraged to implement substantive environmental management practices. Otherwise, they may suffer serious administrative penalties and lose policy support (Yi and Wu, 2022).…”
Section: Management Optimistic Expectationsmentioning
confidence: 99%
“…Scott's new institutional perspective highlights the importance of institutional pressures in strategically shaping the way firms engage in social and environmental practices (Scott, 2001;Shahab et al, 2018) With increasing pressure for legitimacy, firms may change their understanding of environmental issues and increase their investment in environmental protection (Li, 2000). Furthermore, to maintain relationships with the local government and strive for more government support in tax incentives, credit financing, and government subsidies, firms may increase environmental investment and change their production decision-making and resource allocation models to meet the government's expectations (Kumar & Shetty, 2018;Yi & Wu, 2022). On the other hand, the APNRA pilot program will bring another layer of pressure in intensifying market competition and increase the cost of environmental governance for firms in the area.…”
Section: Liter Ature Re Vie W and Hyp Othe S E S De Velopmentmentioning
confidence: 99%
“…This result suggests that when the central government uses the APNRA pilot program to intervene in environmental issues, local officials in the pilot cities are pressured by the program, imposing higher environmental requirements on local firms for their political promotion. After receiving the “signal” of environmental responsibility, local firms, to maintain their relationship with the government and their competitiveness, follow regulations, change production decisions and resource allocation patterns, and actively increase their environmental investment to attain legitimacy (Kumar & Shetty, 2018; Yi & Wu, 2022).…”
Section: Empirical Analysismentioning
confidence: 99%